Diversification options with cassava, maize, and pulses in upland rice based cropping systems in highlands in Madagascar - CGIAR Research Program on Rice (2019)
In 2019, 2 NGOs and farmers’ groups (> 300) visited the experiments in the mid-west of Vakinankaratra. The suitable options identified by farmers are bi-annual upland rice cropping systems rotated with 3 pulses and 2 cover crops in sole crops or in intercropping with maize or cassava.